2018
DOI: 10.1186/s13058-018-1051-6
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and resistance exercise improves physical fitness, bone health, and quality of life in overweight and obese breast cancer survivors: a randomized controlled trial

Abstract: BackgroundExercise is an effective strategy to improve quality of life and physical fitness in breast cancer survivors; however, few studies have focused on the early survivorship period, minorities, physically inactive and obese women, or tested a combined exercise program and measured bone health. Here, we report the effects of a 16-week aerobic and resistance exercise intervention on patient-reported outcomes, physical fitness, and bone health in ethnically diverse, physically inactive, overweight or obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
224
2
32

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(270 citation statements)
references
References 34 publications
12
224
2
32
Order By: Relevance
“…The most common manifestations in postoperative BC patients are mental fatigue, anxiety, and depression [2][3][4]. Moreover, the physical inactivity due to weakness and upper extremity function limitation after surgery may cause the decrease in muscle strength and cardiorespiratory endurance, and then seriously affect the mood and QOL of BC patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The most common manifestations in postoperative BC patients are mental fatigue, anxiety, and depression [2][3][4]. Moreover, the physical inactivity due to weakness and upper extremity function limitation after surgery may cause the decrease in muscle strength and cardiorespiratory endurance, and then seriously affect the mood and QOL of BC patients [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…All 15 trials were RCTs (Adams et al, 2018;Cormie et al, 2015;Dieli-Conwright et al, 2018;Galiano-Castillo et al, 2016;Hojan et al, 2016;Hwang et al, 2008;Kampshoff et al, 2015;Monga et al, 2007;Paulo et al, 2019;Penttinen et al, 2019;Pinto et al, 2005;Schmidt et al, 2015;Segal et al, 2009;Shobeiri et al, 2016;Steindorf et al, 2014). Table 2 reviews all patient details.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…905 patients were randomized in an intervention group (IG1+IG2) and 749 were randomized in a control group of which 36 received a basic recommendation for exercise (Galiano-Castillo et al, 2016) and 142 followed relaxation treatment (Paulo et al, 2019;Schmidt et al, 2015;Steindorf et al, 2014 (Dieli-Conwright et al, 2018;Galiano-Castillo et al, 2016;Hwang et al, 2008;Paulo et al, 2019;Penttinen et al, 2019;Pinto et al, 2005;Schmidt et al, 2015;Shobeiri et al, 2016;Steindorf et al, 2014), in 4 reported prostate cancer (Cormie et al, 2015;Hojan et al, 2016;Monga et al, 2007;Segal et al, 2009), in 1 reported testicular cancer (Adams et al, 2018), in 1 multiple cancer (Kampshoff et al, 2015). In 8 trials patients were still undergoing different therapies (Cormie et al, 2015;Hojan et al, 2016;Hwang et al, 2008;Monga et al, 2007;Paulo et al, 2019;Schmidt et al, 2015;Segal et al, 2009;Steindorf et al, 2014), in 3 trials patients completed therapies (Kampshoff et al, 2015;Penttinen et al, 2019;Shobeiri et al, 2016) and in 4 trials patients were analysed after therapies (Adams et al, 2018;Dieli-Conwright et al, 2018;Galiano-Castillo et al, 2016;Pinto et al, 2005). Exercise interventions lasted from 5 weeks (Mendes et al, 2018) to 5 years (Penttinen et al, 2019), of which 11 trials did follow-up at baseline and after treatment…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Most articles on the obesity treatment relate physical activity with diet (Maffiuletti et al, 2005;Swendeman et al 2018;Dieli-Conwright, et al, 2018), indicating that study participants lose their weight without being able to determine if it's for food reasons or for physical training performed. Sillanpää et al (2008) compared the effects of a training program based on aerobic resistance, strength training, and a third one of mixed application that combined muscle strength and cardiorespiratory resistance on adult men, recording a loss of fat mass in all programs and in special in the aerobic work.…”
Section: Introductionmentioning
confidence: 99%